Synthesis and electroactivated addressing of ferrocenyl and azido-modified stem-loop oligonucleotides on an integrated electrochemical device. (10th May 2015) - Zamfir, Lucian-Gabriel; Fortgang, Philippe; Farre, Carole; Ripert, Micaël; De Crozals, Gabriel; Jaffrezic-Renault, Nicole; Bala, Camelia; Temple-Boyer, Pierre; Chaix, Carole
Abstract: We report a strategy to address stem-loop oligonucleotides on a gold surface in order to develop a robust and ultra-sensitive integrated electrochemical DNA sensor. Probe immobilization relies on the potential-assisted copper-catalyzed alkyne-azide cycloaddition. Firstly, a tetrathiol-hexynyl derivative was used to introduce alkyne functions onto the electrode surface. This anchor has proved its robustness in conditions used for the "click" reaction and in wet storage. Then, different ferrocenyl and azido-modified stem-loop oligonucleotides were synthesized using the solid-phase synthesis technique and their immobilization was studied. Hybridization assays with the DNA target were performed in a complex medium by cyclic voltammetry. The detection sensitivity achieved by our functionalized electrodes was significantly increased, as a detection limit of 10 fM was determined. We also demonstrated that grafting of the stem-loop oligonucleotides via the electroactivated "click" reaction was specific to the gold surface on a microfabricated electro chemical device for the Lab-on-Chip application that fully integrates Au working microelectrodes, Pt counter and Ag reference electrodes.